An Analysis of Students’ Speaking Ability in Using Duolinguo Application - Lisan, Khusnul; Nur Hanifah , Septiani (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
This study aims to identify how is the procedure of using Duolingo application for learning speaking skill, students’ perspective after learning speaking skill using it and the evaluation of learning speaking skill using Duolingo application. This research is using qualitative method with case study approach. Data collection techniques in this study are observation, interview, questionnaire, and documentation with research subjects namely the grade 11th of IPA 2b female students of Madrasah Aliyah Assalafiyyah II Terpadu and also the English teacher. The results of this study were the procedure of using Duolingo application by the students in MA Assalafiyyah II Terpadu. In addition, the students had positive perspectives on the use of Duolingo application because the students are more motivated to learn English. Meanwhile, the evaluation of learning using Duolingo application was in the form a formative assessment by giving feedback directly to the students and also summative assessment by giving retest to the students where the result was increasing in three meetings starting from 53 %,65 %, and 77 % respectively from the test. This showed that the students improved their speaking skills by learning English using this application.